KINERJA PERAWAT DI RUANG RAWAT INAP RSU SARAH KOTA MEDAN DITINJAU DARI GAYA KEPEMIMPINAN DAN KOMUNIKASI KEPALA RUANGAN - Pahala J Simangunsong; Nurul Wahyuni; Diah Ayu Souchi; Rihan Wirda Asdani; Perry Boy Chandra Siahaan; Masryna Siagian; Mafe Robbi Simanjuntak (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2020)
Nursing performance is a work achievement shown by nurses in order to produce good output for patients and the nurses themselves, in this case the head of the room is a component that plays an important role in producing good performance. The initial survey conducted by researchers by distributing questionnaires, it was found that many nurses said the head of the room did not appreciate the work progress achieved by nurses, there was no reprimand made to nurses who made mistakes, the head of the room never gave a reward as an acknowledgment of the nurse's performance. . The head of the room also does not want to accept comments and suggestions from the nurse, the head of the room does not show things that can attract nurses' work interest, the head of the room does not carry out routine supervision of nursing tasks performed by nurses. This research was conducted at the Medan City Sarah General Hospital in 2020 with the aim of knowing the relationship between leadership style and communication of the head of the room with the performance of inpatient nurses. The design of this study was an analytic survey using a cross sectional design with 25 respondents. The research sample was taken using total sampling that is taking the total population of the respondents. Based on statistical tests using the chi-square test, the results of the leadership style with the performance of inpatient nurses with a value of Ï-value (1,000)> 0.05 and communication with the performance of inpatients with the results of Ï-value (0.002) <0.05. The conclusion from the above research is that there is a significant relationship between the head of the room communication with the performance of inpatient nurses and there is no significant relationship between the leadership style of the head of the room and the performance of inpatient nurses.